2002
DOI: 10.1097/00004694-200201000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to determine the effectiveness of the Charleston bending brace when compared with the thoracolumbosacral orthosis (TLSO or Boston) brace in the treatment of single-curve adolescent-type idiopathic scoliosis. The Charleston and TLSO braces were applied for approximately 8 nighttime hours and 18 to 22 hours per day, respectively. Treatment success was defined as improvement of curve deterioration with <5 degrees progression from the start of brace therapy until the conclusion of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…However, a comparison of bracing with electrostimulation showed a higher effectiveness of the former therapy [19]. A comparison of various braces (Charleston Bending Brace, Milwaukee) did not reveal a significant advantage of any of them [20-22]. Finally, recent Cochrane Database of Systematic Reviews publication revealed a low quality evidence in favour of using bracing [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, a comparison of bracing with electrostimulation showed a higher effectiveness of the former therapy [19]. A comparison of various braces (Charleston Bending Brace, Milwaukee) did not reveal a significant advantage of any of them [20-22]. Finally, recent Cochrane Database of Systematic Reviews publication revealed a low quality evidence in favour of using bracing [23].…”
Section: Introductionmentioning
confidence: 99%
“…The Charleston brace is a nighttime-only bending brace that has been shown to be effective in controlling curve progression in multiple studies 812. Biomechanical analysis has shown that significant compressive stress relayed to the spine on the convexity of the scoliotic curve tensile stress on the concavity 13.…”
mentioning
confidence: 99%
“…also found that the TLSO was superior at preventing curve progression when compared with the Charleston brace 49. Gepstein et al .,50 however, found no statistical difference in the surgery rate of 13.5% using the TLSO when compared with surgery rate of 11% using the Charleston brace 50. Similarly, Janicki et al .…”
Section: Brace Typesmentioning
confidence: 95%
“…Hooper and Reed6464752 collaborated in 1978 on the early development of this new side-bending brace for nocturnal wear 174647495052. The orthosis is asymmetrical and fights against the body’s curve by over-correcting the deformity.…”
Section: Brace Typesmentioning
confidence: 99%
See 1 more Smart Citation